The Effectiveness of Law Enforcement In Uncovering Human Trafficking Cases For Organ Trade To Cambodia - M. Yusuf Daeng M; Yusuf, M. Fadly Daeng; Sitorus, Hendrik; Shamer, Chika; Handayani, Erika Yusticia; Suryani, Yovie (Dinasti Research, 2025)
A major crime violating laws and human rights is human trafficking for the organ sales goal. This crime is not limited to one nation but has become international involving Cambodia as a destination. As a victim source, Indonesia has controlled the ban on human trafficking in Law No. 21 of 2007, strengthened even more by Law No. 1 of 2023 and the Health Law No. 36 of 2009. Law enforcement implementation still presents several difficulties, though, including poor cross-border coordination, evidence collecting difficulties, and inadequate protection of witnesses and victims. Operating methodically by taking advantage of legal gaps and socioeconomic weaknesses in national and international systems, organ trafficking syndicates use To lower this crime, cross-border cooperation, law enforcement agency capacity building, and public awareness raising are absolutely vital. To lower the illicit demand for human organs, a legal and open organ donation system is also absolutely vital. The efficiency of law enforcement in exposing cases of human trafficking for organ sales to Cambodia is investigated in this qualitative study employing descriptive techniques. The findings show that although the legal system is strong, structural and operational difficulties still constitute main hurdles in the fight against this crime